CFHR2‐rs2986127 as a genetic protective marker for acute anterior uveitis in Chinese patients. (August 2016) - Huang, Xiu‐Feng; Wang, Yuqin; Li, Fen‐Fen; Lin, Dan; Dai, Ma‐Li; Wang, Qing‐Feng; Jin, Zi‐Bing
Abstract: Background: Complement factor H (CFH) related proteins (CFHRs) play important roles in complement activation pathways, whereas previous studies have only shown that CFH can affect the development of uveitis. In the present study, we investigated the potential associations between one of single‐nucleotide polymorphisms in the CFHR 2 gene with acute anterior uveitis (AAU). Methods: A total of 571 subjects, 283 patients diagnosed with AAU and 288 healthy adult controls, were recruited for this case–control study. CFHR 2‐rs2986127 was detected using Sequenom MassARRAY technology (Sequenom, San Diego, CA, USA). Results: The stratified analyses for AAU patients with ankylosing spondylitis (AS) revealed a reduced frequency of the A allele in CFHR 2‐rs2986127 compared to controls ( p = 0.033, odds ratio = 0.563, 95% confidence interval = 330–0.960). Further stratified analyses revealed a similar significantly reduced frequency in male AAU patients with AS compared to male controls ( p = 0.036, odds ratio = 0.514, 95% confidence interval = 0.274–0.965) and in AAU patients without posterior segment involvement compared to controls ( p = 0.048). Conclusions: The present study reveals an association between CFHR 2‐rs2986127 and AAU diagnosis, especially with respect to gender, AS status and other clinical signs, such as posterior segment involvement. Our results may further enrich the growing understanding of uveitis genetics, and raise the clinical diagnostic accuracy of this disease. Copyright © 2016 John Wiley & Sons, Ltd.